A rapid, simple, high-performance liquid chromatography method for the clinical measurement of beta-lactam antibiotics in serum and interstitial fluid. Issue 6 (26th January 2023) - Riezk, Alaa; Wilson, Richard C.; Rawson, Timothy M.; Vasikasin, Vasin; Arkel, Paul; Ferris, Trevor J.; Haigh, Lisa D.; Cass, Anthony E. G.; Holmes, Alison H.
Abstract : A LC/MS method for the simultaneous quantitative measurement of three beta-lactam antibiotics in serum and interstitial fluid samples. Abstract : Background : enhanced methods of therapeutic drug monitoring are required to support the individualisation of antibiotic dosing based on pharmacokinetics (PK) parameters. PK studies can be hampered by limited total serum volume, especially in neonates, or by sensitivity in the case of critically ill patients. We aimed to develop a liquid chromatography–mass spectrometry (LC/MS) analysis of benzylpenicillin, phenoxymethylpenicillin and amoxicillin in single low volumes of human serum and interstitial fluid (ISF) samples, with an improved limit of detection (LOD) and limit of quantification (LOQ), compared with previously published assays. Methods : sample clean-up was performed by protein precipitation using acetonitrile. Reverse phase chromatography was performed using triple quadrupole LC/MS. The mobile phase consisted of 55% methanol in water + 0.1% formic acid, with a flow rate of 0.4 mL min −1 . Antibiotics stability was assessed at different temperatures. Results : chromatographic separation was achieved within 3 minutes for all analytes. Three common penicillins can now be measured in a single low-volume blood and ISF sample (15 μL) for the first time. Validation has demonstrated the method to be linear over the range 0.0015–10 mg L −1, with an accuracy of 93–104% and high sensitivity, with LOD ≈ 0.003 mg L −1 and LOQ ≈ 0.01 mg L −1 for all three analytes, which is critical for use in dose optimisation/individualisation. All evaluated penicillins indicated good stability at room temperature over 4 h, at (4 °C) over 24 h and at −80 °C for 6 months. Conclusion : the developed method is simple, rapid, accurate and clinically applicable for the quantification of three penicillin classes.